AB1332 Factors associated to persistence on golimumab in patients with inflammatory arthritis of the biobadaser registry. (12th June 2018) - Hernández, M.V.; Rodriguez, S.; Morlà, R.; Sánchez-Piedra, C.; Sánchez-Alonso, F.; Manero, F.J.; García-Magallón, B.; Pérez-Pampín, E.; Rodríguez-Lozano, C.; Ruiz, M.D.; Ortiz, A.; Díaz-Torné, C.; et al.
Abstract : Background: Persistence to treatment may be used as a surrogate marker for long-term treatment success Objectives: To assess the probability of persistence on golimumab (GOL) up to 5 years after treatment initiation and the factors associated to longer persistence Methods: BIOBADASER is the Spanish registry of biological drugs of the Spanish Society of Rheumatology and the Spanish Medicines Agency. A data-base analysis was done in October 2017 on all the patients who had initiated GOL for one of the approved indications (rheumatoid arthritis [RA], axial spondyloarthritis [SpA] or psoriatic arthritis [PsA]). The probability of persistence was calculated with a Kaplan-Meier test. Factors related to persistence were analysed with a Cox-regression model. Results: 353 patients were included (105 [29.8%] RA, 147 [30.6%] axial SpA and 101 [28.6%] with PsA), mean age 52 11 years, 55% women). Median duration of disease at the onset of GOL was 8.0 [2.8–15.0] years. GOL was the first biological drug in 40.1% of the patients, second in 30.1% and third or further biological in 29.8%. Concomitant medication at GOL initiation was methotrexate (MTX) (33.7%), sulphasalazine (SSZ) (6.1%), leflunomide (LEF) (12.7%), steroids (CS) (26.0%). At the last observation on GOL, 32.0% were on MTX, 5.8% on SSZ, 12.8% on LEF, 16.3% on CS. The probability of persistence on GOL since treatment initiation was 85.9% at year 1 (95% CI 81.4–89.5), 73.7% at year 2 (67.1–79.1), 68.5% at year 3 (60.5–75.1), 60.6% (50.2–69.5) at year 4% and 57.1% (44.9–67.5) at year 5. Persistence was similar for RA, axial SpA or PsA patients (p log-rank 0.070), and higher when GOL was used as first biological agent (p log-rank <0.001). As first biological drug the probability of persistence was 94.5% (year 1) and 85.4% (year 2), (insufficient number of cases to assess persistence at year 3 or further). As second biological drug, it was 89.8% (year 1), 75.2% (year 2), 67.4% (year 3) and 59.2% (year 4) and as third biological drug the figures were, respectively, 69.6%, 58.4%, 54.5% and 46.1%. Cox-regression analysis (table 1) showed that the probability of persistence on GOL therapy was higher in first vs second or third biological line patients (Hazard Ratio for discontinuation [HR]: 2.30 [95% CI: 1.16–4.55] for second and 3.92 [2.07–7.39] for third line), and in patients with concomitant MTX (HR discontinuation=0.55 [0.33–0.91]), and lower in those needing CS (HR discontinuation=2.83 [1.72–4.66]). Conclusions: In patients with RA, axial SpA or PsA, the probability of persistence on GOL after initiation was high. The retention rate was higher both in patients with GOL as first biological drug and in those with concomitant therapy with MTX, and lower in those needing CS. Acknowledgements: This study was funded by Merck Sharp and Dohme of Spain Disclosure of Interest: None declared